Foucault's philosophy of art a : genealogy of modernity - Tanke, Joseph J. (London : Continuum, 2009)
Contents: The stirrings of modernity##Rupture##Nonaffirmative painting##Anti-platonism ##The cynical legacy.
Onderzoek KASK Professioneel (OFVP)
boek
Keywords: Foucault, Michel